Controlling of compliant grinding for low-rigidity components. (May 2020) - Yang, Yue; Li, Haonan; Liao, Zhirong; Axinte, Dragos; Zhu, Wule; Beaucamp, Anthony
Abstract: The machining of low-rigidity components (e.g. thin-walled) with compliant tools presents accuracy challenges as both sides in contact are being deformed. The controlling method presented in this paper enables, for the first time, to obtain the desired and uniform material removal rate by controlling the nominal tool offset when two bodies (workpiece and tool) are compliant in grinding. A contact deformation model is proposed to predict the relation between the nominal and actual tool offsets. The function of nominal tool offsets and material removal rates is obtained based on the calibration tests. Spot grinding tests have been performed for the validation of the calculated material removal rates, normal grinding forces and spot sizes, presenting position-dependent characteristics. The controlling method has been tested for the case of continuous grinding the whole area of a circular aluminium thin wall. The surfaces ground under the time-variant tool offsets (proposed approach) reach the desired removal depth with an average error of ≤10% and achieve 11.2 μm–24.2 μm (P–V) accuracy in the elastic domain, compared with the error of 76.8%~113.7% and accuracy of 42.6 μm–50.1 μm (P–V) in the circumstance of constant tool offsets (conventional approach). Graphical abstract: Image 10148 Highlights: A theoretical contact model for the first time was proposed for grinding involving two compliant bodies. The model reveals the position-variant characteristics of the relation between nominal and actual tool offsets. This paper proposed a new control strategy by time-variant tool offset design to obtain a constant material removal rate. The ground surfaces obtained from the proposed strategy reach the desired removal depth with an average error of ≤10%.